2017
DOI: 10.1177/1534734617737660
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Laboratory Findings of Lower Extremity Amputation in Diabetic Patients: Meta-analysis

Abstract: Lower extremity amputation is a source of morbidity and mortality among diabetic patients. This meta-analysis aimed to identify significant laboratory data in patients with diabetic foot ulcer with high rates of lower extremity amputation. We performed a systematic literature review and meta-analysis using MEDLINE, EMBASE, and Cochrane databases. We extracted and evaluated 11 variables from the included studies based on amputation rates. This study used the Newcastle-Ottawa Scale to assess the quality of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Matthews et al demonstrate this in Table 3 in their paper [10] by estimating the number of amputations in subgroups that did not have independent risk factors for amputation identified in CANVAS and CANVAS-R, including male sex, non-Asian ethnicity, prior amputation, peripheral vascular (probably artery) disease, neuropathy, albuminuria and poorer glucose control. These risk factors for amputation are largely consistent with prior reports [2][3][4][5][6][7][8], as mentioned earlier in this commentary.…”
Section: The Design Of Canvas and Canvas-r And Implications For Clinisupporting
confidence: 91%
See 1 more Smart Citation
“…Matthews et al demonstrate this in Table 3 in their paper [10] by estimating the number of amputations in subgroups that did not have independent risk factors for amputation identified in CANVAS and CANVAS-R, including male sex, non-Asian ethnicity, prior amputation, peripheral vascular (probably artery) disease, neuropathy, albuminuria and poorer glucose control. These risk factors for amputation are largely consistent with prior reports [2][3][4][5][6][7][8], as mentioned earlier in this commentary.…”
Section: The Design Of Canvas and Canvas-r And Implications For Clinisupporting
confidence: 91%
“…Diabetic foot ulcers usually occur due to a direct or indirect trauma associated with loss of protective sensation and are frequently accompanied by peripheral artery disease. Several factors increase the risk of LEA in diabetic individuals with or without diabetic foot ulcers, such as male sex, sensory neuropathy, peripheral artery disease, prior history of foot ulcer or amputation, poor glycaemic control, renal dysfunction, non-Asian ethnicity and presence of infection [2][3][4][5][6][7][8]. Recently, the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, in which individuals were randomised to receive intensive therapy (HbA 1c <42 mmol/mol [<6%]) or standard glycaemic control (HbA 1c 53-63 mmol/mol [7.0-7.9%]), showed that the intensive regimen resulted in a significant decrease in LEA risk and that mean HbA 1c strongly predicted LEA occurrence [9].…”
Section: Introductionmentioning
confidence: 99%
“…3 What’s more, before amputations, 85% of diabetic patients have a foot ulcer and severe infection of diabetic foot ulcer is likely to increase the risk of amputation. 4,5 This disease has a profound influence on patient’s quality of life and implies a high cost to the patient and insurance providers. Mobility limitation, pain and discomfort feelings are the primary determinants for poor overall health-related quality of life.…”
mentioning
confidence: 99%
“…One of the crucial medical, social, and economic problems prevalent, particularly in developing countries like Saudi Arabia, is diabetic foot ulceration (DFU) and related infections, which are the principal causes for patient morbidity and mortality. 1-4 From earlier studies, it is evident that 15% of all diabetic patients suffer from foot ulcer at some time in life, making them highly predisposed to rapidly spreading infections, which culminate in almost uncontrollable tissue destruction and finally amputation. 5,6…”
mentioning
confidence: 99%